Radical Behaviorism in Organizations: Misconceptions in the Locke-Gray Debate - Parmerlee, Marcia; Schwenk, Charles R. (Academy of Management Review, 1979)
The authors examine how behaviorism has been studied as a theory of human behavior. They set forth their argument of radical behaviorism in organizations and discuss some of the misconceptions of Locke in his examination of behaviorism. They examines these issues in four categories; Locke's interpretation of behavior modification, epiphenomenalism, rejection of introspection and determinism. They also address the work of psychologist B. F. Skinner and examine his views on behaviorism. The authors believe that there exists a great deal of misunderstanding over radical behaviorism and aim to clear up what they see as the most fundamental issues.